A novel cis-regulatory element regulates αD and αA-globin gene expression in chicken erythroid cells - Cortés-Fernández de Lara, Josué; Núñez-Martínez, Hober Nelson; Tapia-Urzúa, Gustavo; Garza-Manero, Sylvia; Peralta-Alvarez, Carlos Alberto; Furlan-Magaril, Mayra; González-Buendía, Edgar; Escamilla-Del-Arenal, Martín; Casasola, Andrea; Guerrero, Georgina; Recillas-Targa, Felix (Frontiers in Genetics, 2024)
Cis-regulatory elements (CREs) are key players in erythroid cell differentiation. In this work, we compared genome-wide chromatin accessibility between proerythroblasts (HD3) and embryonic fibroblasts and we identified a novel erythroid-specific intergenic cis-regulatory element, which we refer to as CRE-2, embedded in the chicken α-globin loci. CRE-2 was enriched in active enhancer-associated histone marks throughout terminal erythroid differentiation. Using UMI-4C, we observed that CRE-2 is located within an interacting region encompassing the α-globin genes. By CRISPR-Cas9-mediated genomic editing, we deleted the CRE-2 in HD3 cells and observed that CRE-2 is required for proper αD and αAgene expression in HD3 cells and upon differentiation. Our findings demonstrate that cell-specific CREs contribute to the fine-tuning regulation of erythroid cell-specific genes.